Individual characteristics on multicultural team performance: does the role played by leaders and team members matter? - Guzmán-Rodríguez, Laura Esmeralda; Arizkuren-Eleta, Amaia; Agarwala, Tanuja; Bornay-Barrachina, Mar (Frontiers in Psychology, 2023)
The main purpose of this study was to analyze the impact of individual characteristics of cultural sensitivity, adaptability, cohesion, and cultural diversity on the multicultural team performance. Also, we analyzed the moderating effect of being a team member or a team leader on the relationships mentioned above. To test out hipotheses, data were collected from 415 members of multicultural teams specifically, from 304 team members and 111 leaders. The findings provided evidence to support a positive relationship between cultural sensitivity, adaptability, cohesion, and team performance. Cultural diversity did not show a significant impact on team performance. The study also showed that the leaders and members had different perceptions about the factors that influence team performance. For instance, team members consider that cohesion influences team performance, while leaders consider adaptability as the key factor to achieve performance. Main implications from findings are discussed.